Q: Remove the parentheses and simplify 11x - 7x - 5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

11x+9=7x+21 11x-7x=4 4x+9=21 21-9=12 4x=12 12 divided by 4= 3 x=3

If: 11x+25 = 7x+15 then there is only one solution and it is x = -2.5

First of all, let's agree on what the question is ...The question is: What's the number for 'x' that makes this statement true ?Here's how to find it:11x - 4 = 7x + 16Add 4 to each side:11x = 7x + 20Subtract 7x from each side:4x = 20Divide each side by 4:x = 5

4x + 8 + 7x + 12 = 11x + 20

x=3

Related questions

As there are no parentheses then the expression stated can be simplified as follows :- 7x - 4x - 9 = 3x - 9 If the parentheses were placed (7x - 4x) - 9 then the result would be the same. If the parentheses were placed 7x - (4x - 9) = 7x - 4x + 9 = 3x + 9.

11x - 21 = 7x + 3 4x = 24x = 6

7x + 8 = 11x + 3, solve for xsubtract 7x from both sides8 = 11x - 7x + 38 = 5x + 3subtract 3 from both sides5 = 5xdivide both sides by 51 = x.

11x+9=7x+21 11x-7x=4 4x+9=21 21-9=12 4x=12 12 divided by 4= 3 x=3

If: 11x+25 = 7x+15 then there is only one solution and it is x = -2.5

First of all, let's agree on what the question is ...The question is: What's the number for 'x' that makes this statement true ?Here's how to find it:11x - 4 = 7x + 16Add 4 to each side:11x = 7x + 20Subtract 7x from each side:4x = 20Divide each side by 4:x = 5

4x + 8 + 7x + 12 = 11x + 20

x2+11x+11 = 7x+9 x2+11x-7x+11-9 = 0 x2+4x+2 = 0 The above quadratic equation can be solved by using the quadratic equation formula and it will have two solutions.

x=3

X2+11x+11 = 7x+9 X2+11x-7x+11-9 = 0 x2+4x+2 = 0 Solve as a quadratic equation by using the quadratic equation formula or by completing the square: x = -2 + or - the square root of 2

11x + 2 = 26 + 7x Subtract 7x from both sides: 4x + 2 = 26 Subtract 2 from both sides: 4x = 24 Divide both sides by 4: x = 6

4x + 6 = -82 - 7X add 7X to each side 4X + 7X + 6 = -82 -7X + 7X 11X + 6 = -82 subtract 6 from each side 11X + 6 - 6 = -82 - 6 11X = -88 divide both sides by 11 X = -8 check in original equation 4(-8) + 6 = -82 - 7(-8) -32 + 6 = -82 + 56 -26 = -26 checks